Inhibition of inducible nitric oxide synthase-derived nitric oxide as a therapeutical target for acute pancreatitis induced by secretory phospholipase A(2) - Camargo, E. A.; Santana, D. G.; Silva, C. I.; Teixeira, S. A.; Toyama, M. H. [UNESP]; Cotrim, C. [UNESP]; Landucci, E. C. T.; Antunes, E.; Muscara, M. N.; Costa, S. K. P. (Wiley-Blackwell, 2014)
BackgroundNitric oxide is a key signalling molecule in the pathogenesis of inflammation, but its role in acute pancreatitis and related abdominal pain induced by secretory phospholipase A(2) (sPLA(2)) from Crotalus durissus terrificus (Cdt) venom has not been investigated.MethodsMale Wistar rats were i.v. injected with L-NAME (20 mg/kg), aminoguanidine (AG, 50 mg/kg), 7-nitroindazole (7-NI, 10 mg/kg) or vehicle 10 min before or 60 min after the injection of sPLA(2) (300 mu g/kg) into the common bile duct. After 4 h of sPLA(2) injection, abdominal hyperalgesia and inflammation were assessed in addition to serum amylase, nitrite/nitrate (NOx), pancreas lipoperoxidation and 3-nitrotyrosine (3-NT) contents.ResultssPLA(2)-induced acute pancreatitis, related abdominal hyperalgesia, hyperamylasemia and increased concentration of NOx were not correlated with lipoperoxidation or increased 3-NT in the pancreas. Pretreatment with all the nitric oxide synthase (NOS) inhibitors significantly reduced abdominal mechanical hyperalgesia, but only iNOS blockade by AG suppressed pancreas oedema and serum NOx increase. The therapeutic approach with all the NOS inhibitors produced a similar reduction pattern of the abdominal hyperalgesia, but AG treatment also inhibited serum hyperamylasemia and NOx concentrations and pancreatic myeloperoxidase. The nNOS blockade by 7-NI treatment also inhibited myeloperoxidase activity in both pancreas and lung.ConclusionsTherapeutic blockade of iNOS or nNOS provides benefits in terms of inhibition of the acute pancreatitis-related abdominal hyperalgesia, while iNOS inhibition also ameliorates the inflammatory cell influx to the pancreas and reduces the resultant hyperamylasemia and NOx levels, thus representing alternative pharmacological strategies for treatment of clinical pancreatitis associated with increased PLA(2).